A New Mayfly Species of Epeorus (Caucasiron) from Southwestern China (Ephemeroptera: Heptageniidae) - Chen, Ping; Wang, Yu-Yu; Zhou, Chang-Fa (Zootaxa, 2010)
The mayflies of the subgenus Epeorus (Caucasiron) are lotic aquatic insects in Heptageniidae. They are unique in the family because their gills form a disc, gills 1 are strongly expanded anteriorly and contiguous under thorax, gills 7 have a longitudinal fold and are contiguous under apex of abdomen and the pairs of gill 2–6 or 7 have a distinct projection on anterior-dorsal side of leading margin as well as imaginal tubular, diverging penis lobes with titillators. A new species, Epeorus (Caucasiron) extraordinarius sp. nov., collected from southwestern China, is described here. The strongly expanded anterior portion and the concave lateral margins of the nymphal head capsule, the color pattern of nymphs and imagos, and the structure of the male genitalia with relatively small titillators distinguish the new species from previously described members of the subgenus.